(untitled) (Research, Society and Development, 2021)
The use of agrochemicals has influenced the increase in agricultural productivity. However, the concern about damage to the human health and to the environment, resulting from the indiscriminate use of pesticides, has increased worldwide. Alternative methods for controlling pests and diseases have been proposed to maintain productivity and quality of life. A possibility is to use compounds produced by the secondary metabolism of plants, such as the essential oils. Some of these substances perform inhibitory or stimulatory activity on the development of other organisms. Plants from the genus Eucalyptus have been investigated and were chosen to be studied in the present work, due to the traditional knowledge regarding the potential of the essential oils from some species, as well as, for the need to use residues from their production. Therefore, were determined the yield, identified the compounds from the essential oils of E. urophylla and the hybrid E. urophylla x E. camaldulensis, and evaluated their biological activity through bioassays, investigating the phyto-cyto-genotoxicity and mutagenicity using Lactuca sativa and Sorghum bicolor as model plants. The essential oil from the hybrid provided a higher yield. Eucalyptol was the major compound identified for both oils, representing more than 85% of the compounds present. Both E. urophylla and the hybrid showed phyto-cyto-genotoxic, mutagenic effects, and clastogenic and aneugenic mechanisms of action, promoting epigenetic changes in the meristematic cells of L. sativa. The results point out to the bioherbicidal potential of these essential oils.